2019
DOI: 10.17267/2596-3368dentistry.v10i1.2268
|View full text |Cite
|
Sign up to set email alerts
|

The influence of oral conditions on quality of life of adolescents: an integrative review

Abstract: INTRODUCTION: During adolescence, changes in oral health status can influence even more the quality of life since in this phase there is greater physical, psychological and social vulnerability, being a moment in which the individual is shaping his identity. OBJECTIVE: to evaluate the level of evidence and scientific knowledge currently available in the literature on the association between the status of the oral condition of adolescents and the quality of life reported by them. METHODOLY: This integrative rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The results of the present study demonstrated negative and significant relationship of both the dental caries degree (DMFT index) and malocclusion severity (ICON score) with OHRQoL, and thus, confirmed the main point of our hypothesis. In contrast to many other studies in this field of research [1,[9][10][11]31,32,35,61], our study was focused on older adolescents, aged 15 to 18, which is the key novelty of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study demonstrated negative and significant relationship of both the dental caries degree (DMFT index) and malocclusion severity (ICON score) with OHRQoL, and thus, confirmed the main point of our hypothesis. In contrast to many other studies in this field of research [1,[9][10][11]31,32,35,61], our study was focused on older adolescents, aged 15 to 18, which is the key novelty of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The number of studies on the impact of malocclusion on OHRQoL in the field of orthodontics is also growing rapidly [31]. There have been many studies demonstrating that orthodontic anomalies can negatively affect the OHRQoL of children and adolescents [31][32][33][34][35]. However, there is a debate in the literature on how these affects depend on the methods of malocclusion assessment (subjective or objective; level of orthodontic treatment need; what index of the orthodontic treatment need was used) [36].…”
Section: Introductionmentioning
confidence: 99%